INTRODUCTION OF INTERNET OF THING TECHNOLOGY BASED ON PROTOTYPE - Genadiarto, Anthony Sutera; Noertjahyana, Agustinus; Kabzar, Vladimir (Jurnal Informatika, 2017)
Internet of thing has been able to attract people compete to create various devices. Devices developed have various benefits, but the point is to make life easier. So many vendors create products related to the internet of things, so the user gets confused to determine which is good and appropriate for the needs. To simplify the user in choosing IoT product, this research will discuss about technology that is widely used in IoT, the advantages of each technology, in terms of security, operating system, microcontroller, IoT platform, tools and communication technology. This research makes prototype with one of existing technology. The results of this research provide knowledge, skills and experience in the field of IoT as well as information related to IoT technology, which is widely in the market. Furthermore, the prototype also has the expected functionalities, but it does not close the opportunity for further improvements. The results of this research provide knowledge, skills and experience in the field of IoT as well as information related to IoT technology, which is widely in the market. Furthermore, the prototype also has the expected functionalities, but it does not close the opportunity for further improvements.